Effect of Monitoring Techniques on Project Performance of Kenyan State Corporations - Wanjala, Muchelule Yusuf; Iravo, Mike Amuhaya; Odhiambo, Romanus; Shalle, Noor Ismail (European Scientific Journal, ESJ, 2017)
Monitoring practices are the continuous routine in the tracking of key elements of project implementation performance that is: inputs (resources, equipment) activities and outputs, through recordkeeping and regular reporting through assessment of an on-going or completed project to determine its actual impact against the planned impact in relation to its design, implementation, and results. However, monitoring practices implementation has been a challenge over years, organizations have crumbled due to failure to master monitoring best practices in the performance of their projects. The main objective of this study is to investigate the influence of monitoring techniques on project performance of Kenyan State Corporations. Simple random sampling was used to select 65 state corporations which form the sample size. Data were collected from the sample size using questionnaires with both open and closed questions. The data were analyzed using descriptive and inferential statistics as well as qualitative methods. The relationships between variables were determined using person correlation and t-test. Assessments of normality were done by Shapiro-Wilk test. Findings showed that Monitoring techniques (β3= 0.674, p<0.05) has significant affect project performance.